Distinct antigen uptake receptors route to the same storage compartments for cross‐presentation in dendritic cells. Issue 3 (30th June 2021) - Ho, Nataschja I.; Camps, Marcel G.; Garcia‐Vallejo, Juan J.; Bos, Erik; Koster, Abraham J.; Verdoes, Martijn; van Kooyk, Yvette; Ossendorp, Ferry
Abstract: An exclusive feature of dendritic cells (DCs) is their capacity to present exogenous antigens by MHC class I molecules, called cross‐presentation. Here, we show that protein antigen can be conserved in mature murine DCs for several days in a lysosome‐like storage compartment, distinct from MHC class II and early endosomal compartments, as an internal source for the supply of MHC class I ligands. Using two different uptake routes via Fcγ receptors and C‐type lectin receptors, we could show that antigens were routed towards the same endolysosomal compartments after 48 h. The antigen‐containing compartments lacked co‐expression of molecules involved in MHC class I processing and presentation including TAP and proteasome subunits as shown by single‐cell imaging flow cytometry. Moreover, we observed the absence of cathepsin S but selective co‐localization of active cathepsin X with protein antigen in the storage compartments. This indicates cathepsin S‐independent antigen degradation and a novel but yet undefined role for cathepsin X in antigen processing and cross‐presentation by DCs. In summary, our data suggest that these antigen‐containing compartments in DCs can conserve protein antigens from different uptake routes and contribute to long‐lasting antigen cross‐presentation. Abstract : Antigens taken up by dendritic cells via Fcγ receptors or C‐type lectin receptor MGL1 are routed towards the same endolysosomal compartments, which express LAMP1 and active cathepsin X. These compartments can conserve antigen for several days and serve as an antigen depot for prolonged antigen cross‐presentation to CD8 + T cells.